Saber cotidiano X saber científico : um estudo com adultos alunos da educação de jovens e adultos - EJA - Camargo, Janira Siqueira (2014)
The objective of this study was to analyze the role of Adult Education in the transformation of everyday knowledge in scientific knowledge, using psychoeducational assessment in adult learners. For both, were evaluated psicopedagogicamente eleven adult students from three classes EJA from a school located in Maringá through the following instruments: anamnesis, Projective Tests Psychopedagogical (Pair Education, Family Education, Drawing Episodes), operational tests (change in criteria, class inclusion, intersection of classes, grading, length conservation, conservation of matter, conservation of fluid, conservation of discrete quantities, conservation area, conservation of weight, conservation of volume, combination and permutation) and Test School Performance - TDE. With the results we found that adults who did not attend school at the right age and whose cognitive structures were not built in childhood, either by lack of education, either by inadequate access opportunities situations enabling it to this construction, it is more difficult in the process of school learning in adult education. His thinking is grounded in immediate experience, pledging to raise hypotheses or abstract propositions such that, EJA need to provide learning situations in which the adult range scientific thinking through education aimed at meeting the characteristics of their students.